Stratégies d’adaptation d’adolescents lors de mauvais traitements psychologiques - Cynthia Bêty; Francine Lavoie; Danielle Nadeau (Sociétés et Jeunesses en Difficulté)
In spite of the studies conducted on coping strategies, results remain unsatisfactory both in the domain of theory and practice. The present study addresses some of the criticisms that have been made by contributing to reflections on the conceptualization of coping strategies. Coping strategies are investigated in a clinical population of adolescents in the context of a particular stressor, namely, psychological maltreatment. In order to accomplish this, 19 young people between the ages of 12 and 18 who had attempted suicide, were recruited at a Youth Centre. Content analysis enabled us to identify 12 conceptual categories grouped under three adaptive processes: situation management, internal management, social resources management. Discussion of the results is done by comparing the particular features of the categories and groupings with the models available in the literature. Practical recommendations are also made.